"For a few minutes I could pretend I was someone else" - a study of multiple approaches to fiction reading activities - Jannike Bakke; Fride Lindstøl (Cappelen Damm Akademisk NOASP, 2021)
This empirical study researches a literary reading process. 8th grade pupils participate in a close reading of a short story, Magrete Kind (Zwilgmeyer, 1895), in which they engage with different types of fiction reading activities (Norwegian: "fiktive lesemåter"). The process takes place in a professional workshop, an arena for working systematically with teaching quality in teacher education. The purpose of this article is to contribute to knowledge about the composition of experience-based processes in reading fiction, where the pupil's reader role becomes visible. The study is anchored in literary and dramaturgical theory, and fictionalization is central. The dramaturgical analyses show that the pupils like to work collectively and in role. They also enjoy working bodily and spatially, and are positive about staging and remediating the short story. Their approach to text is often text-external, and they are oriented towards thematic and relational layers of meaning. The remediation of the short story gives the students a good text experience, but this means that they move away from the original narrative.